Guidelines for best practice: Imaging for age estimation in the living. (March 2019) - Doyle, Edel; Márquez-Grant, Nicholas; Field, Lisa; Holmes, Trish; Arthurs, Owen J; van Rijn, Rick R.; Hackman, Lucina; Kasper, Kathleen; Lewis, Jim; Loomis, Peter; Elliott, Denise; Kroll, Jeroen; et al.
Highlights: X-rays of the hand/wrist have been the 'gold standard' for skeletal age estimation. Non-ionising modalities such as MRI and ultrasound have been considered recently. Combining physical examinations with imaging is the most accurate approach. Software is now available and can be utilised to estimate skeletal age.